Diversity, Equity, and Inclusion in Introductory Statistics Courses: Results from a National Survey - Heather Barker; Kirsten Doehler; Julia Walter (Journal of Statistics and Data Science Education)
Statistics instructors have a unique opportunity to engage students in work around Diversity, Equity, and Inclusion (DEI) since there is an abundance of data that can be incorporated into courses with DEI contexts. An online survey was conducted to explore how faculty teaching introductory college statistics integrate DEI into their courses. About 300 participants reflected on their institution’s priorities related to DEI and what has aided and constrained them from incorporating DEI practices when teaching statistics. We found that 77% of participants indicated that they do include DEI practices in their teaching. Results show that participants at research intensive institutions are least likely to incorporate DEI, and those that have more years of teaching experience are less likely to incorporate DEI into their courses. Constraints that prevent instructors from incorporating DEI-related activities include lack of resources and time and concern about student discomfort. Additionally, those who felt most prepared to incorporate DEI were typically individuals who had engaged in professional development focused on DEI and teaching. Since there has not been a survey of this nature, these results will be useful as a metric for the inclusion of DEI into introductory statistics classes.